Effect of camber on badminton shuttlecock - Konishi, Y.; Matsushima, Y.; Misaka, T.; Okuizumi, H.; Tanaka, K.; Obayashi, S. (Proceedings, 2018)
In this study, we conducted experimental measurements and computational analysis to investigate the aerodynamics of a shuttlecock, especially the effects of the camber of the shuttle`s skirt. The static aerodynamic coefficient from the experiment showed that the camber of the skirt was able to modify the aerodynamic characteristics. A positive camber, which indicates bending the blade toward the outside, causes a slight increase in lift and a decrease in drag. On the other hand, a negative camber causes an increase in drag, and an insensitive region in the lift and a pitching coefficient of approximately 0° was observed. This result leads to instability in the flight of the shuttlecock. The pressure distribution calculated using computational fluid dynamics revealed that each blade functions as a two-dimensional airfoil. However, in most cases, the blade is in stall condition due to an initial divergence angle of the skirt.